THE IMPORTANT ROLE OF ENTREPRENEURSHIP EDUCATION IN ENCOURAGING INTENTION TO INNOVATE (CASE STUDY ON STUDENT BUSINESS PROJECT) - Namira, Velanska Dixie; Setiobudi, Auditia (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
One way to improve the Indonesian economy is to increase the number of entrepreneurs so that the number of businesses running is also increasing. But along with the increasing number of businesses in Indonesia, innovation is needed so that these businesses can survive in the market. This study aims to determine the relationship between personality traits and entrepreneurial learning that has been obtained on the intention or intention to innovate on the business project being run. The study sample size was 168 respondents. Researchers use Smart-PLS 4.0 software in data processing. The results of the study found that entrepreneurial education and personality traits have a significant impact on innovation intention. Personality traits will increase the influence of entrepreneurial education on innovation intention. This research is expected to be the basis for future research on innovation intention considering the lack of research that discusses it.